Inventarisasi Lichen Crustose Epifit pada Tanaman Teh di Kecamatan Ngargoyoso Kabupaten Karanganyar - Fitri Izzatu Roniyah; Efri Roziaty (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Lichens or lichens are organisms that are the result of a symbiotic relationship between algae (photobionts) and fungi (mycobionts). Because it is very sensitive to pollution, epiphytic lichen is often used as a bioindicator of air pollution in a location. This study aims to determine the types of epiphytic crustose lichen on tea plants in Ngargoyoso District, Karanganyar, Central Java. This study used a population of lichens in the Kemuning Ngargoyoso Tea Plantation, Karanganyar. The sample used was epiphytic crustose lichen at the Kemuning Ngargoyoso Tea Plantation, Karanganyar, and the sampling technique was purposive sampling. In determining the location is divided into 3 stations. Station 1 (900 m asl), station 2 (1,000 m asl), and station 3 (1,100 m asl). Lichen distribution is affected by altitude, therefore more and more lichen colonies are found at higher altitudes. The parameters used in this study were crustose lichen, crustose lichen morphology and crustose lichen habitat. This type of research is descriptive exploratory. The research data obtained were analyzed descriptively qualitatively by presenting them in the form of tables and figures.